Impact of exercise training without caloric restriction on inflammation, insulin resistance and visceral fat mass in obese adolescents. Issue 4 (4th August 2014) - Mendelson, M.; Michallet, A.‐S.; Monneret, D.; Perrin, C.; Estève, F.; Lombard, P. R.; Faure, P.; Lévy, P.; Favre‐Juvin, A.; Pépin, J.‐L.; Wuyam, B.; Flore, P.
Summary Background Exercise training has been shown to improve cardiometabolic health in obese adolescents. Objectives Evaluate the impact of a 12‐week exercise‐training programme (without caloric restriction) on obese adolescents' cardiometabolic and vascular risk profiles. Methods We measured systemic markers of oxidation, inflammation, metabolic variables and endothelial function in 20 obese adolescents (OB) (age: 14.5 ± 1.5 years; body mass index: 34.0 ± 4.7 kg m−2) and 20 age‐ and gender‐matched normal‐weight adolescents (NW). Body composition was assessed by magnetic resonance imagery. Peak aerobic capacity and maximal fat oxidation were evaluated during specific incremental exercise tests. OB participated in a 12‐week exercise‐training programme. Results OB presented lower peak aerobic capacity (24.2 ± 5.9 vs. 39.8 ± 8.3 mL kg−1 min−1, P < 0.05) and maximal fat oxidation compared with NW (P < 0.05). OB displayed greater F2t‐Isoprostanes (20.5 ± 6.7 vs. 13.4 ± 4.2 ng mmol−1 creatinine), Interleukin‐1 receptor antagonist (IL‐1Ra) (1794.8 ± 532.2 vs. 835.1 ± 1027.4 pg mL−1), Tumor Necrosis Factor‐α (TNF‐α) (2.1 ± 1.2 vs. 1.5 ± 1.0 pg mL−1), Soluble Tumor Necrosis Factor‐α Type II Receptor (sTNFαRII), leptin, insulin, homeostasis model assessment of insulin resistance, version 2 (HOMA2‐IR), high‐sensitive C‐reactive protein, triglycerides and lower adiponectin and high‐density lipoprotein cholesterol (all P < 0.05). After exercise training, despite lack of weight loss, VO2peak (mL.kg−1.min−1) and maximal fat oxidation increased (P < 0.05). IL‐1Ra and IFN‐gamma‐inducible protein 10 (IP‐10) decreased (P < 0.05). Insulin and HOMA2‐IR decreased (14.8 ± 1.5 vs. 10.2 ± 4.2 μUI mL−1 and 1.9 ± 0.8 vs. 1.3 ± 0.6, respectively, P < 0.05). Change in visceral fat mass was inversely associated with change in maximal fat oxidation (r = −0.54; P = 0.024). The subgroup of participants that lost visceral fat mass showed greater improvements in triglycerides, insulin resistance and maximal fat oxidation. Conclusion Our data confirms the role of exercise training on improving the inflammatory profile and insulin resistance of OB in the absence of weight loss. However, those who lost a greater amount of visceral fat mass showed greater benefits in terms of insulin profile, triglycerides and maximal fat oxidation.